Evaluating Business and Industry Training
320 p.
Keywords: In the abstract, training is seen as valuable by most people in business and industry. However, in the rush of providing training programs "on time" and "within budget," evaluation of training is frequently left behind as a "nice to have" addition, if practical. In addition, the training function itself is left with the dilemma of proving its worth to management without a substantive history of evaluation. This book is designed to provide managers, educators, and trainers alike the opportunity to explore the issues and benefits of evaluating business and industry training. The purpose is to motivate more effective decisions for training investments based on information about the value of training in attaining business goals. Without evaluation, the value of specific training efforts cannot be adequately measured, the value of training investments overall cannot be fully assessed, and the contributions of the training function to the corporation's goals cannot be duly recognized. Articles are grouped into three sections, althou~h many themes appear across sections. The first section estabhshes the context of training evaluation in a business organization. The second section emphasizes evaluation of training products and services; and the third section discusses costs and benefits of evaluation, and communication and use of evaluation results in decision making. In Section I, the context of training evaluation is established from a variety of perspectives. First, training and trainin~ evaluation are discussed in the context of corporate strateglc goals.